2005
DOI: 10.1007/s00595-004-2927-x
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing Papillary Carcinoma Arising in a Lingual Thyroid: Report of a Case

Abstract: Ectopic lingual thyroid tissue is an uncommon congenital anomaly. Tumors with identical pathological characteristics to those arising in thyroid tissue may be present in ectopic locations, but there are very few cases of malignant ectopic thyroid tumors reported in the literature. We present a review of this phenomenon and report a case of papillary carcinoma of the base of the tongue, located in ectopic lingual thyroid tissue, in a 30-year-old woman. The patient's presenting symptoms were dysphagia and oral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Many authors reported the clinical and cytopathological features of this entity [6,12,13]. Only a few case reports and small series regarding this entity correlating with imaging findings have been reported in the literature [10,14,15]. However, the report of sonographic features of this entity in larger series is rare.…”
Section: Discussionmentioning
confidence: 91%
“…Many authors reported the clinical and cytopathological features of this entity [6,12,13]. Only a few case reports and small series regarding this entity correlating with imaging findings have been reported in the literature [10,14,15]. However, the report of sonographic features of this entity in larger series is rare.…”
Section: Discussionmentioning
confidence: 91%
“…Although lingual thyroid has been reported in 10% of autopsies, it is an uncommon clinical problem, with an incidence ranging from 1 in 4,500 to 1 in 100,000 3 . Hickman described the first case in 1869, and, to date, approximately 400 cases have been reported in the literature 8,9 . It can become symptomatic at any age but usually during puberty, menses, or pregnancy, perhaps because of increased metabolic demand 6,9 .…”
Section: Discussionmentioning
confidence: 99%
“…3 Hickman described the first case in 1869, and, to date, approximately 400 cases have been reported in the literature. 8,9 It can become symptomatic at any age but usually during puberty, menses, or pregnancy, perhaps because of increased metabolic demand. 6,9 Patients typically present with dysphagia, dysphonia, dyspnea, and oral hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…94 Primary thyroid carcinomas including papillary and follicular have been reported to arise within ETTs. 90,[95][96][97] The distinction of a primary thyroid neoplasm arising de novo in ectopic thyroid tissue from a cervical lymph node metastasis can be challenging. In 1 study morphologically normal thyroid adjacent to neoplastic areas within a laterocervical site in patients with a primary thyroid tumor was positive for CK19, Gal-3, and HBME-1 whereas these markers were negative in the normal tissue adjacent to neoplastic tissue in laterocervical masses in patients with no evidence of a primary thyroid tumor.…”
Section: Ectopia/heterotopia/choristomamentioning
confidence: 99%